2019
DOI: 10.1111/hepr.13349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 10‐year changes in liver stiffness using vibration‐controlled transient elastography in non‐alcoholic fatty liver disease

Abstract: Aim Although liver biopsy is the gold standard for the diagnosis and staging of non‐alcoholic fatty liver disease (NAFLD), repeated assessment of patients’ liver tissue conditions are impractical. We assessed the 10‐year changes in liver stiffness measurements (LSM) utilizing vibration‐controlled transient elastography in NAFLD patients. Methods From January 2006 to September 2007, LSM was carried out for 97 biopsy‐proven NAFLD patients. Of these, 34 patients underwent 10‐year LSM reassessments (14 of them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
0
12
0
1
Order By: Relevance
“…A response to pharmacological intervention was defined as a decrease in ALT of >30% compared with baseline after 6 months of PEM treatment according to several NAFLD clinical trials [ 21 , 22 ]. We compared the baseline clinical features of PEM responders (n = 40) and non-responders (n = 48) in HTG-NAFLD patients, including those who underwent body composition analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A response to pharmacological intervention was defined as a decrease in ALT of >30% compared with baseline after 6 months of PEM treatment according to several NAFLD clinical trials [ 21 , 22 ]. We compared the baseline clinical features of PEM responders (n = 40) and non-responders (n = 48) in HTG-NAFLD patients, including those who underwent body composition analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although VCTE is a blind technique, it is the most commonly used technique for screening, treatment monitoring, and longitudinal follow-up in various chronic liver diseases, and is the best-validated elastography modality worldwide. In patients with NAFLD, repeated measurements of liver stiffness made using VCTE are useful for long-term monitoring and the prediction of liver-related complications and cardiovascular events [18,19]. In addition, repeated measurements of liver stiffness can reduce false-positive diagnosis of advanced fibrosis in patients with NAFLD [20,21].…”
Section: Vibration-controlled Transient Elastographymentioning
confidence: 99%
“…To the best of our knowledge, our study was the first study to evaluate the long-term treatment responses of NAFLD to bariatric surgery using TE as a monitoring tool. In the literature, TE had been tested on the roles of monitoring disease progression and response to treatment of NAFLD [21][22][23][24][25] . Suzuki et al reported the changes of LSM over 4 years in 36 patients without paired liver biopsies for monitoring disease progression of NAFLD 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, histopathological correlation with paired liver biopsies was not available. Nogami et al evaluated the disease progression of NAFLD in terms of fibrosis stage using LSM in 34 patients over 10 years 22 . Based on LSM, 32.4% of patients had progression in fibrosis stage and 17.6% had improvement.…”
Section: Discussionmentioning
confidence: 99%